Fragmented QRS as a predictor of cardiac events in patients with cardiac sarcoidosis. Issue 3 (March 2022) - Ogura, Soichiro; Nakamura, Kazufumi; Morita, Hiroshi; Nakagawa, Koji; Nishii, Nobuhiro; Akagi, Satoshi; Toh, Norihisa; Takaya, Yoichi; Yoshida, Masashi; Miyoshi, Toru; Watanabe, Atsuyuki; Ito, Hiroshi
Highlights: Cardiac sarcoidosis (CS) is at higher risk of sudden cardiac death from ventricular arrhythmia. Fragmented QRS (fQRS) is a predictor of ventricular arrhythmic events in patients with CS. No association between hospitalization for heart failure and fQRS was observed in CS. Abstract: Background: : Multiple spikes within the QRS complex, known as fragmented QRS (fQRS), are associated with the occurrences of ventricular arrhythmic events (VAEs) in patients with Brugada syndrome and hypertrophic cardiomyopathy. However, the association between fQRS and occurrence of VAEs in patients with cardiac sarcoidosis (CS) has not been elucidated. Methods: : We evaluated the associations between fQRS and cardiac events including VAEs [non-sustained ventricular tachycardia (NSVT), sustained ventricular tachycardia (VT), and ventricular fibrillation (VF)], hospitalization for heart failure, and all-cause death in 68 patients with CS (30 patients with fQRS vs. 38 patients without fQRS) over a 5-year period. Results: : Cardiac events occurred in 22 patients with fQRS and 18 patients without fQRS (73% vs. 47%, p =0.009). Of the cardiac events that occurred in CS patients, VAEs occurred more frequently in patients with fQRS than in patients without fQRS (VAEs: 70% vs. 45%, p =0.017; NSVT: 70% vs. 45%, p =0.010; VT: 43% vs. 18%, p =0.011, and VF: 6.7% vs. 2.6%, p =0.34), whereas there was no significant difference in hospitalization for heart failure or all-cause death between patients with and those without fQRS (hospitalization for heart failure: 6.7% vs. 5.3%, p =0.75; all-cause death: 6.7% vs. 5.3%, p =0.64). Multivariate analysis showed that fQRS in the baseline electrocardiogram was independently associated with VAEs (hazard ratio: 2.21, 95% confidence interval: 1.15–4.25, p =0.017). Conclusion: : fQRS is a predictor of VAEs in patients with CS. Graphical abstract: Image, graphical abstract